School attendance zones as a method for promoting educational equity - Mason, Abigail (Kansas State University, 2022)
Historically, school attendance zones have been gerrymandered in a similar way to political boundaries, generally fostering inequities in access to educational opportunities and thus youth outcomes. Yet, in response to proven benefits of integrated schools, some public-school districts now seek to implement integration plans that will diversify their student bodies. These integration plans often involve redrawing attendance zones to promote economic and racial equity between schools. However, drawing attendance zones based on demographic factors rather than geographic location may generate unintended consequences and public pushback. This leads to the question, “Is redistricting public school attendance zones an effective method for promoting educational equity?”. This question is investigated with a literature review of equity in school attendance zone planning and a case study analysis of Manhattan-Ogden USD 383’s recent redistricting efforts. USD 383’s redistricting efforts, which took place for the 2021-2022 school year, are analyzed for equity with a narrative of the redistricting process and a data analysis. Through an analysis of the redistricting process, it is determined that USD 383’s main goals in redistricting were to promote equity in class size distribution and building usage with the secondary goal of increasing demographic diversity within schools. In response, data analysis is conducted within and between USD 383’s ten elementary schools for three equity-related variables (enrollment, socio-economic status, and racial demographics) to analyze change from the 2020-2021 to 2021-2022 school years. The data suggests that most schools experienced minimum change in these equity-related variables after redistricting because public pushback to progressive redistricting plans resulted in the adoption of new attendance zones that largely maintained the status quo. The results of this study suggest that school attendance zones may have the potential to promote educational equity, but in reality, prove difficult to use for achieving specific goals because of external social and political factors.
Keywords: Education; Area planning and development; Urban planning; Education history; Education planning; Equity